The impact of the application of accounting systems based on IAS / IFRS international accounting standards on management control - Namoun , Mohamed Azzedine; Al-djabiri, Abdellah Hassen; baala, Tahir (Journal of Research in Finance and Accounting, 2020)
The adoption of the financial accounting system has a positive impact on the company, indeed, the financial statements and the financial information produced by this system are of quality, but this cannot be achieved if it does not exist coordination between accountants and management controllers to achieve this objective. The management controller has a major role in the application of the accounting and financial system, he makes the changes to the information system so that it is adapted to the requirements of this system and he participates in the preparation of the financial statements, in fact, the management controller becomes an information provider for the accounting department, so that the accounting department can prepare the financial statements and produce reliable and quality information. Also, financial accounting for the management controller is a database for measuring, evaluating and controlling the performance of the company.